SELF-REGULATION AS A FACTOR OF CONSTRUCTED ORAGNIZATIONS` SUSTAINABLE DEVELOPMENT - T. Shemyakina (Вестник университета, 2019)
The legislative base of transition to self-regulation in construction has been analyzed. Differences and advantages of admission to works from the construction license, problems of control of construction works on objects performance, scopes of the state supervision have been considered. The procedure of SRO participation in identification and response to the violations, allowed by the construction organization, has been investigated. Functions of construction control and their difference from technical supervision have been considered. The criterion for the selection of effective self-regulatory organizations, the introduction of preventive control, combining the functions of construction control and supervision of the customer and self-regulatory organization have been offered.